A new subspecies, Eumeces schneiderii barani n. ssp (Reptilia: Sauria: Scincidae) from Turkey - Kumlutas, Yusuf; Arikan, Hüseyin; Ilgaz, Çetin; Kaska, Yakup (Zootaxa, 2007)
This study describes a new subspecies of lizard, Eumeces schneiderii barani n. ssp., from western Anatolia, Turkey. The new subspecies is differentiated from other two subspecies in Anatolia (E. s. princeps and E. s. pavimentatus) by its characteristic colour and colour-pattern as well as by the scales along the dorsal midline. Results obtained from polyacrylamide gel disc electrophoresis support this differentiation.